2D/3D Halide Perovskites for Optoelectronic Devices - Chen, Xiang; Zhou, Hai; Wang, Hao (Frontiers in Chemistry, 2021)
The traditional three-dimensional (3D) halide perovskites (HPs) have experienced rapid development due to their highly power conversion efficiency (PCE). However, the instability of 3D perovskite on humidity and UV irradiation blocks their commercialization. In the past few years, two-dimensional (2D) halide perovskites attract much attention because they behave better stability due to the water resistance of the aliphatic carbon chains in the 2D perovskite lattice. In this review, we categorize the 2D/3D perovskites based on the applications (i.e., solar cells (SCs), light-emitting diodes (LEDs) and photodetectors (PDs)). We further discuss the recent efforts in the performance enhancement of the 2D/3D perovskite-based devices. However, there are still some difficulties before 2D/3D HPs is fully commercialized. We will provide some scientific and technical challenges and prospects in the article to point out the future direction.